Influence of the SLC6A3-DAT1 Gene on Multifaceted Measures of Self-regulation in Preschool Children - Cómbita, Lina M.; Voelker, Pascale; Abundis-Gutiérrez, Alicia; Pozuelos, Joan P.; Rueda, M. Rosario (Frontiers in Psychology, 2017)
Development of self-regulation, the capacity to voluntarily modulate thoughts, emotions and actions is strongly related to the maturation of the dopamine-mediated executive attention network (EAN). The attention control processes associated with the EAN greatly overlap with efficiency of the executive functions and are correlated with measures of effortful control. Regulation of dopamine levels within the EAN, particularly in the basal ganglia is carried out by the action of dopamine transporters. In humans, the SLC6A3/DAT1 gene carries out the synthesis of the DAT protein. The 10-repeat allele has been associated with an enhanced expression of the gene and has been related to ADHD symptoms. Little is known about the impact of DAT1 variations on children’s capacity to self regulate in contexts that impose particular demands of regulatory control such as the school or home. This study defines a multi-domain phenotype of self-regulation and examines whether variations of the DAT1 gene accounts for individual differences in performance in 4-5 year old children. Results show that presence of the 10r allele is related to a diminished ability to exert voluntary regulation of reactivity. These findings shed light on the neurobiological mechanisms underlying individual differences in self-regulation during childhood.